The Constitution as a Reflection of National Identity and Character - Yunus, Nur Rohim (ADALAH, 2023)
The constitution reflects a nation's identity and character, reflecting its people's values, history, and ideals. As the highest fundamental law, the constitution regulates various aspects of national and state life, including the system of government, human rights, and the obligations of citizens. This essay discusses how the Constitution is a legal guideline and a symbol of national identity. The history of constitutional changes reflects social and political dynamics, showing how the nation adapts to the times without losing its fundamental values. This essay also reviews the importance of every citizen's understanding and practice of the Constitution so that everyday life's values are truly realised. Thus, the constitution is not only a legal document, but also the soul that shapes the character and direction of the nation's future.